Guess again - Donlea, Charlie (Kensington Publishing Corp., 2025)
"Ten years after teen volleyball star Callie Jones vanished without a trace, former detective Ethan Hall is pulled back to his haunted hometown to uncover long-buried secrets forcing him into a dangerous investigation with ties to his own dark past"--